"Providing a perspective that's a little bit different": Academic and professional experiences of male speech-language pathologists. (2nd January 2021) - Azios, Jamie H.; Bellon-Harn, Monica
Abstract: Purpose: A significant gender imbalance exists in the profession of speech-language pathology and the perspectives of male speech-language pathologists are underrepresented in the professional literature. This study explored the role of gender as a factor related to the academic and professional experiences of male speech-language pathologists working in the United States. Method: Phenomenology was used to understand factors influencing the lived experiences of males in the profession. In-depth semi-structured interviews were collected from fifteen male speech-language pathologists and subjected to inductive thematic analysis. Result: Four superordinate and thirteen subordinate themes emerged from the data. Findings suggest that males experience challenges working in a female-dominated profession. That said, males highlighted their progression towards inclusion in the profession and overall perceived their academic and professional life as positive and rewarding. Participants valued the distinctive quality of being male in a female-dominated profession and described a sense of empowerment by virtue of being male. Conclusion: A gender disparity remains present in the field of speech-language pathology, which limits the ability to best serve a diverse population and creates health disparities. While participants reported many challenges working in a female-dominated profession, these obstacles appeared to motivate rather than hinder work-related performance and overall job satisfaction. The themes presented here help to develop a deeper understanding of the perspectives of males in the field and the specific factors that contribute to their experiences. Additionally, these data can inform future strategies for recruitment and retention of males in the profession.